CARDIOVASCULAR EFFECTS OF CENTRALLY ACTIVE CHOLINOMIMETICS IN CONSCIOUS AND ANESTHETIZED RATS - THE ROLE OF AMYGDALA - YEGEN, BERRAK (PERGAMON-ELSEVIER SCIENCE LTD, 1995)
Central cardiovascular effects of cholinergic agonists depend on the dose, site and mode of administration, species, and to the state of the animal. Intravenous injection of physostigmine and intracerebroventricular injection of carbachol produced presser and tachycardic responses in urethane-anesthetized rats. Both agents also elicited presser responses in conscious rats, but bradycardia occurred in the presence of anesthesia, Additionally, presser responses to physostigmine, but not to carbachol, were significantly exaggerated by urethane anesthesia. These results demonstrate that anesthesia depresses cardiovascular reflexes and the inhibitory control mechanisms on acetylcholine release from the nerve endings involved in cardiovascular regulation. The role of the central nucleus of the amygdala (CNA) was also investigated in this study. The presser effects of intracerebroventricular injection of carbachol were significantly attenuated by electrolytic ablation of the CNA, but heart rate changes were not altered both in anesthetized and conscious rats. These results indicate that the CNA plays a role in cholinergic control of blood pressure, but not in the regulation of heart rate.
Keywords: AMYGDALA; CHOLINERGIC HYPERTENSION; CHOLINOMIMETICS; PHYSOSTIGMINE; CARBACHOL; BLOOD PRESSURE; HEART RATE; ANESTHESIA; RAT; NUCLEUS TRACTUS SOLITARII; CENTRAL NERVOUS-SYSTEM; CHOLINERGIC MECHANISMS; HYPERTENSIVE RESPONSE; MUSCARINIC RECEPTORS; BRAIN ACETYLCHOLINE; PRESSOR-RESPONSE; STIMULATION; CARBACHOL; PHYSOSTIGMINE